PERBANDINGAN SISTEM PEMERINTAHAN DAN PENDIDIKAN MASA DINASTI UMMAYAH DAN DINASTI ABASIYAH - Azizah Puspa Ningrum; Nuryuana Dwi Wulandari (Jambura History and Culture Journal, 2023)
The purpose of this research is to examine the comparison of government and education systems in two dynasties, namely the Ummayad dynasty and the Abbasid dynasty. Government and education systems are interrelated things in a country. In the Umayyad and Abbasid dynasties, there were differences in the system of government and education. The researcher uses the library research method, which involves the analysis and synthesis of information from written sources such as books, journals and other materials. The results of this study are to know: (1) Ummayah dynasty system of government, (2) Ummayah dynasty education system, (3) Abbasid dynasty system of government, (4) Abbasid dynasty education system, (5) Comparison of government and education systems in the two periods Ummayad dynasty and Abbasid dynasty.